A Comparative Analysis of Effect of Statins in Cardiovascular Patients on Root Canal Calcification Using CBCT: A Retrospective Study - Neha, Neha; Gupta, Alpa; Abraham, Dax; Ahmad, Lubna (European Journal of General Dentistry, 2025)
Root canal calcification (RCC) occurs as a diffuse phenomenon, making endodontic treatment challenging. Various factors like systemic diseases and medication induce the calcification process. It has been stated in studies that statin causes odontoblastic differentiation of human dental pulp stem cells, causing RCC. The objective of the study was to evaluate and compare RCC in healthy individuals and cardiovascular patients with and without statin therapy using cone-beam computed tomography (CBCT).This retrospective study comprises three groups in which group 1 consisted of healthy individuals, group 2 consisted of cardiovascular patients not taking statin medication, and group 3 consisted of cardiovascular patients taking statin medication. The study included healthy first or second mandibular molar. CBCT was utilized to detect the RCC in terms of volume measurement among all the groups.For inferential analysis, a one-way analysis of variance and post hoc Tukey's test will assess the significance of sample means against known values.The pairwise comparison revealed that there is no significant difference between group 1 and group 2, and comparatively, group 3 significantly has higher calcification (least volume) than groups 1 and 2 in both mandibular first and second molar.Systemic medications like statin possess an increased risk of RCC due to odontoblastic differentiation of human dental pulp stem cells. CBCT should be employed as a diagnostic tool for accurate diagnosis of RCC and correlating systemic oral illness and facilitating early diagnosis.
Keywords: cardiovascular disease; cone-beam computed tomography; root canal calcification; statin